Assumptions of India’s Foreign Policy and Their Evolution During the ‘Cold War’ (Economic and Political Thought, 2014)
In the 21st century, India is more and more often perceived as a statewith a growing political, economic and military potential, which togetherwith China may dominate the international arena in the future. Indiastarted to accentuate its position in international relations 60 years ago sosuch a scenario would be its crowning achievement in its aspiration to bea superpower. The first Indian Prime Minister Jawaharlal Nehru’s policyof non-alignment, promotion of peace and world development in the 1950saimed to establish India’s leadership. Although the priorities of India’sforeign policy were reformulated because of the changing regional and globalconditions during the cold war (including the American-Pakistani-Chinesealliance), the state has never abandoned its aspirations to be a superpower. Itshould be remembered that contemporary strategy of India’s development isnot only a result of reforms initiated in the 90s but also a legacy of the policydeveloped during the cold war, oscillating between idealism and realism.